(untitled) (Revista del Instituto de Investigación Musicológica "Carlos Vega", 2025)
This work addresses the critical edition of two musical compositions by Rosa Borja de Ycaza, a key figure in the world of art, education, and political activism in the city of Guayaquil during the early years of the 20th Century. To understand the context of the work and its author, a historical review is presented on the condition of Ecuadorian women during the republican era and Rosa Borja de Ycaza’s role and influence in the social changes that took place. Likewise, a reflection is made on the activity of critical music editing, its methodology, and its usefulness for the preservation of Ecuadorian cultural heritage. All these concepts are applied to the study of the works under analysis: Elegía and Vals.